Changes in unmet care needs, social support and distress from initial diagnosis to post-surgery in patients with gynecological cancer: A longitudinal study - Adamakidou, Theodoula; Menti, Konstantina; Charalambous, Andreas; Tsiou, Chrysoula; Vlachou, Eugenia; Govina, Ourania (My University, 2023)
This study aimed to explore the changes in unmet care needs, perceived social support, and levels of distress experienced by newly diagnosed Greek patients with gynecological cancer during the phase after diagnosis and before surgical treatment (T0), and 4 months after surgical treatment at the first postoperative follow-up visit (T1).
Keywords: Anxiety; Distress; Gynecological cancer; Longitudinal study; Needs assessment; Newly diagnosed patient; Nursing care; Social support